Changing teaching practices: The impact of a professional development program on an English teacher - Sierra-Piedrahita, Ana María (Íkala, Revista de Lenguaje y Cultura, 2018)
Professional development programs in the form of learning communities offer teachers the possibility to improve their practice and support them in accomplishing the demands that the government and society have assigned them when these are well designed and developed. The study reported here focused on understanding how an English teacher changed her teaching practice with the support of a facilitator in a teacher learning community. Data was gathered through interviews, class observations, recorded meetings and teachers’ planning units and pedagogical materials. Results indicate that the teacher experienced changes in her teaching practice related to patterns of teaching behavior and teaching methodology. However, there were some aspects of these two components that she changed only to a certain extent. Moreover, she underwent some difficulties with students and with some contextual factors that affected her learning process. This study reveals several contributions that a learning community can offer to in-service teachers to improve their teaching practice.